Economic and political aspects of food and crop quality productions - Giacomo Büchi; Teresina Mancuso (Italian Journal of Agronomy)
In this paper will be analyzed – at international, european and national level – the framework of a protection system of geographical indication (Denomination of Protected Origin and Protected Geographical Indication as defined in the EU Regulations, “certified production” in the follow), to highlight the potentials and the limits of their expansion on the world markets. The economy of italian certified agro-food productions and their political issues, will be also investigated.